PENGEMBANGAN KARAKTER KEMANDIRIAN BERIBADAH ANAK MELALUI DIDIKAN SUBUH DI FORUM KOMUNIKASI DINIYAH TAKMILIYAH (FKDT) KECAMATAN PADANG SELATAN - Napriyanti; Rizal Safarudin; Seprian Ilham (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The purpose of this study was to determine the implementation of the Dawn Education program and its role in developing children's religious character and fostering independent religious practice in three Islamic Senior High Schools (MDTA) in South Padang. The study locations were the Syukur Mosque, Mukminin Mosque, and Al-Falah Mosque. The informants were teachers and several students. This study employed qualitative research methods that emphasize the objectivity of the data. Data collection techniques included interviews, observation, and documentation. The results of this study concluded that, first, the management of the Dawn Education program to develop children's religious character in the Syukur Mosque, Mukminin Mosque, and Al-Falah Mosque MDTAs has been quite effective in terms of planning, implementation, and evaluation. This was significantly influenced by various aspects, including internal management, the immediate environment outside the MDTAs, and the commitment of the MDTA administrators. Second, the Dawn Education program systematically plays a role in shaping various aspects of independence, including: instilling an understanding of the value of worship, fostering a spirit of worship, instilling time discipline, and instilling awareness of worship. Third, the character of independent worship among children at the MDTA FKDT Padang Selatan is demonstrated through their devotional activities, including congregational prayer and consistent Dhuha prayer, which are grounded in the values ​​of awareness, responsibility, discipline, and motivation. These character traits are highly influential not only in worship but also in other activities